PENGARUH GAYA KEPEMIMPINAN TERHADAP KUALITAS PENGAMBILAN KEPUTUSAN DALAM ORGANISASI SURAT KABAR KAMPUS GANTO UNIVERSITAS NEGERI PADANG - Taufiqurrahman; Syamsir; Latifah Irbah; Ghaitsa Zahira Shofa; Fauziah Nabilla Iskandar; Amanda Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Leadership is a crucial factor in determining organizational success, particularly in the decision-making process. High-quality decisions enable organizations to achieve their goals effectively and efficiently. This study aims to analyze the influence of leadership style on the quality of decision-making within the Ganto Campus Newspaper Organization at Universitas Negeri Padang. Using a qualitative descriptive approach, data were collected through in-depth interviews with the Chief Leader of Ganto as the primary informant, supplemented by secondary data from academic literature. The findings indicate that the leadership style implemented in Ganto is predominantly participative or democratic. The leader provides opportunities for members to express opinions, considers diverse inputs prior to making decisions, and prioritizes deliberation in resolving organizational issues. This participative leadership style has a significant positive impact on the quality of decision-making by enhancing member participation, broadening the information base used in the decision-making process, reducing internal conflict, improving implementation effectiveness, and strengthening member trust in the leadership. The study concludes that the application of a participative leadership style is a key determinant of effective and high-quality organizational decision-making.